What makes an issue relevant to newspaper editorials? an empirical approach to criteria of editorial-worthiness - Mont'Alverne, Camila; Marques, Francisco Paulo Jamil (Brazilian journalism research, 2022)
ABSTRACT: Although journalism studies rely on a well-grounded debate about news values, there are fewer investigations about the values used to select a topic in newspaper editorials. By tackling the concept of editorial-worthiness, this article aims to empirically examine which editorial values influence how news organizations build their institutional opinions. Methodologically, we use content analysis to find out what makes a topic worth being addressed in 840 editorials published by Folha de S. Paulo and O Estado de S. Paulo (two Brazilian mainstream newspapers) in 2007 and 2017. Our results reveal that “topicality,” “the power elite,” and “conflict” are the most frequent editorial values in both organizations, showing some parallel with news values, although not a complete overlap. Lastly, our framework provides a key contribution to disclosing the similarities and singularities typical of different cultures concerning editorial journalism, offering the opportunity to think about journalism research and practice more broadly. RESUMO – Embora os estudos sobre jornalismo partam de um debate consolidado sobre valores notícia, existem menos investigações a respeito dos valores utilizados para selecionar um assunto em editoriais. Partindo do conceito de editorialidade, este artigo procura examinar empiricamente quais valores editoriais influenciam em como as organizações noticiosas constroem suas opiniões institucionais. Metodologicamente, usamos Análise de Conteúdo para descobrir o que faz um assunto ser abordado em 840 editoriais publicados por Folha de S. Paulo e O Estado de S. Paulo em 2007 e 2017. Os resultados mostram que “topicalidade”, “elites” e “conflito” são os valores editoriais mais frequentes nas duas publicações, mostrando algum paralelo com os valores notícia, embora não haja uma sobreposição completa. Nosso trabalho oferece uma contribuição crucial para revelar similaridades e singularidades típicas de diferentes culturas editoriais, oferecendo a oportunidade de refletir sobre pesquisa e prática jornalística de forma mais ampla. RESUMEN – Aún que los estudios sobre periodismo estén consolidados acerca de los valores noticia, hay menos investigaciones acerca de los valores que se usan para seleccionar un asunto en editoriales. Este artículo parte del concepto de editorialidad para analizar empíricamente que valores editoriales afectan como los media crean sus opiniones institucionales. Nosotros usamos análisis de contenido para averiguar lo que hace que un asunto sea tratado en 840 editoriales publicados por Folha de S.Paulo y O Estado de S. Paulo, dos de los principales periódicos de Brasil. Los resultados muestran que “topicalidad”, “élites”, y “conflicto” son los valores editoriales más frecuentes en los dos periódicos, revelando semejanza con valores noticia, aún que no haya superposición total. Nuestro trabajo ofrece una importante contribución para revelar semejanza y singularidad de distintas culturas editoriales, con la oportunidad de reflexionar acerca de la investigación y practica periodística de forma más amplia.